A CRITICAL REVIEW ON THE PREDICTION OF ELASTIC PROPERTIES OF BICONTINUOUS MATERIALS BASED ON EFFECTIVE MEDIUM APPROXIMATION - Widjajakusuma, Jack (Universitas Gunadarma, 2007)
The purpose of this article is to review some mixing laws based on the effective mediumapproximation in predicting the effective elastic properties of bicontinuous media. Specificattention is assigned to the systematic derivation of these mixing laws exploiting the informationof the microstructures of bicontinuous materials. In order to verify the accuracies of the variousmixing laws, the predicted effective values of real bicontinuous materials are compared to thoseeffective values obtained by finite element simulation.